An identical‐by‐descent novel splice‐donor variant in PRUNE1 causes a neurodevelopmental syndrome with prominent dystonia in two consanguineous Sudanese families. (10th June 2021) - Koko, Mahmoud; Yahia, Ashraf; Elsayed, Liena E.; Hamed, Ahlam A.; Mohammed, Inaam N.; Elseed, Maha A.; Hamad, Muddathir H. A.; Babai, Arwa M.; Siddig, Rayan A.; Abd Allah, Amal S. I.; Mohamed, Mayada; EL‐Amin, Melka; et al.
Abstract: PRUNE1 is linked to a wide range of neurodevelopmental and neurodegenerative phenotypes. Multiple pathogenic missense and stop‐gain PRUNE1 variants were identified in its DHH and DHHA2 phosphodiesterase domains. Conversely, a single splice alteration was previously reported. We investigated five patients from two unrelated consanguineous Sudanese families with an inherited severe neurodevelopmental disorder using whole‐exome sequencing coupled with homozygosity mapping, segregation, and haplotype analysis. We identified a founder haplotype transmitting a homozygous canonical splice‐donor variant (NM_021222.3:c.132+2T > C) in intron 2 of PRUNE1 segregated with the phenotype in all the patients. This splice variant possibly results in an in‐frame deletion in the DHH domain or premature truncation of the protein. The phenotypes of the affected individuals showed phenotypic similarities characterized by remarkable pyramidal dysfunction and prominent extrapyramidal features (severe dystonia and bradykinesia). In conclusion, we identified a novel founder variant in PRUNE1 and corroborated abnormal splicing events as a disease mechanism in PRUNE1‐ related disorders. Given the phenotypes' consistency coupled with the founder effect, canonical and cryptic PRUNE1 splice‐site variants should be carefully evaluated in patients presenting with prominent dystonia and pyramidal dysfunction.